Spacecraft beware: huge spines of ice might guard a glimmering moon. (18th October 2018) - Unknown
Touchdowns on Jupiter's moon Europa, which might host life, could be risky. Touchdowns on Jupiter's moon Europa, which might host life, could be risky.